Solidarity and human nature - Luis Miguel dos Santos Luzio; Bernardo Carlos Spaulonci Chiachia Matos de Oliveira (Serviço Social em Revista, 2010)
The concept of solidarity inhabits the collective unconscious and is usually related to something consensual, linked to the most basic values of mankind, but to expand that understanding leads to more complex views. Human solidarity would be conditioned by biological, or cultural issue that goes beyond any possible biological determinism. This study seeks to analyze the phenomenon of solidarity and its correlation with life in society from the perspective of complexity, through a cross-sectional analysis in order to cover the phenomenon in question from different perspectives. For that, we appealed to sociobiology, and the social sciences interpretation. We tried to thereby renounce the sole idea and permanent solution, by approaching to the assumptions of complex thinking, which rely precisely to overcome a single organizing principle or a single cause to explain the same phenomenon. It noticed the need of new societal experiences, which would block the advance of competitive individualist paradigm as the sole alternative, highlighting the experiences of the solidarity economy and third sector organizations that have a new business logic, a third social force among the state and the market.